Assistance Of Farmers In Utilizing The Consortium Of Endophite Bacteria And Organic Fertilizer As Well Organic Pesticides Based On Local Wisdom To Increase Rice Productivity - Aziez, Achmad Fatchul; Wiyono; Budiyono, Agus (Journal of Community Capacity Empowerment, 2023)
The "Sidodadi" farmer group in Demangan village, Sambi sub-district, Boyolali district consists of 15 members, which is a rainfed farmer group. Paddy productivity in rainfed lowland is quite low (2-3 tons/ha) compared to irrigated land (5 tons/ha). The use of a consortium of endophytic bacteria, organic fertilizers and organic pesticides based on local wisdom and the selection of varieties according to their designation can increase rice productivity. Rice farming in this farmer group does not yet have proper management, so assistance is needed. The purpose of this service is to assist in the management of rainfed land so that their income increases.The problems of this farmer group are 1) Aspects of Production and 2) Aspects of management. Production aspects include (a) Technology Utilization Aspect: not having technology to increase rice productivity (b). Aspects of Soil Fertility: rarely use organic fertilizers (c) Aspects of Use of Varieties: rice varieties that are not suitable for allotment of rainfed rice fields. The solution to the problems that arise is to assist farmer group members to use endophytic bacteria consortia, use organic fertilizers and organic pesticides based on local wisdom, use rice varieties that are suitable for sub-optimal rainfed land and farm management training. This activity will be carried out in two places, 1) in the yard of the farmer group members and 2) in the paddy fields in Demangan village, Sambi sub-district, Boyolali Regency from July 2023 to December 2023. The method used is 1) Farm management counseling and assistance, 2) Practice: making a consortium of endophytic bacteria, organic fertilizers and organic pesticides based on local wisdom 3) Cultivating organic rice in rainfed paddy fields, 4). Monitoring and evaluation. The result of this community-based service activity is an increase in the skills of farmers in making endophytic bacteria, making local microorganism (MOL), making solid organic fertilizers, making liquid organic fertilizers and organic pesticides and selecting rice varieties that are suitable for rainfed lowland rice fields and its application in rainfed lowland rice cultivation.